Penerapan Model Pembelajaran Kooperatif Tipe TGT dengan Media Flash Card untuk Meningkatkan Pemahaman Materi Al-ArqÄm dalam Pembelajaran Bahasa Arab pada Siswa Kelas X MA YPPA Cipulus - Asti Agustina Rahmani; TB. Abdul Hamid (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to know the effectiveness of applying a Teams-Games-Tournament (TGT)-type cooperative learning model with flash card media in improving studentsâ€™ understanding of al-arqÄm material on Arabic language learning. Research uses Classroom Action Research (CRA) method implemented in two cycles, with subjects 25 students of grade X MA YPPA Cipulus. Each cycle consists of four stages, namely planning, execution, observation, and reflection. Instruments used included student engagement observation sheets, field notes, and learning outcome tests. The results of the study showed that applying TGT with the help of flash cards can increase studentsâ€™ activity and understanding significantly. In cycle I, the average student engagement reached 62.8%, while in cycle II it increased to 85.6%, with a percentage increase of 36.3%. This improvement was supported by a more interactive learning atmosphere, more equal student participation, as well as the use of flash card media that facilitated students in understanding Arabic numerals (al-arqÄm). Thus, it can be concluded that the application of TGT-type cooperative learning model with flash card media is effective in improving studentsâ€™ understanding of al-arqÄm material in Arabic language learning in Grade X MA YPPA Cipulus.